Experimental investigation into the use of sodium nitroprusside for controlling polysaccharide fouling in membrane separation. (February 2019) - Xie, Zhangwang; Skillman, Lucy; Nagaraj, Veena; Li, Dan; Ho, Goen
Abstract: Biofouling has been regarded as a great challenge in membrane separation processes, such as reverse osmosis (RO) and forward osmosis (FO). One of the major contributors to biofouling is the extracellular polymeric substances (EPS) produced by bacteria, especially the polysaccharides that form a large part of EPS. This study investigated experimentally the inhibition of polysaccharide fouling by sodium nitroprusside (SNP) in RO and FO using two model polysaccharides, alginate and xanthan. It was hypothesized that NO released from SNP would act as a free radical to decompose polysaccharides and in turn alleviate fouling in membrane separation. Potassium ferricyanide (KFCN), having a similar structure as SNP, was used as a comparison. The results showed that SNP could alleviate polysaccharide fouling and its efficiency was greater than KFCN in reducing polysaccharide fouling of RO, likely due to the NO radical released. The presence of Ca 2+ ions in feedwater increased the extent of fouling by both alginate and xanthan, but SNP was able to alleviate the fouling. Alleviation of polysaccharide fouling in FO was better than in RO under comparable operating conditions. SNP could be considered as a polysaccharide fouling alleviating agent.